ANALISIS KEBUTUHAN PENGEMBANGAN BAHAN AJAR DIGITAL PEMBELAJARAN SEJARAH BERBASIS APLIKASI ANDROID DI SMA - Ridho Bayu Yefterson; Kevin Fallo (Jurusan Sejarah FIS UNP, 2022)
This article aims to analyze the need for developing digital teaching materials for Android-based history learning. The method used in this research is Research and Development (R&D) with the ADDIE model. The research subjects were educators and students at SMA N 2 Padang. The feasibility test of teaching materials involves teaching materials experts and historical materials experts. The practicality test involved a history teacher and 34 participants in SMA N 2 Padang class XI IPA 4. The study was conducted in February-March 2022. The results of field observations, interviews and surveys explained that students were very interested in using the internet to find material. teaching history learning, and educators have limited time, access and lack of site references that present history teaching materials according to the 2013 curriculum, so that the supervision by educators is not optimal for students in accessing the internet to find history learning materials. The results of the needs analysis show that students need digital teaching materials that are in accordance with the 2013 curriculum.